AN INQUIRY INTO IRANIAN ENGINEERING STUDENTS LIFE EXPERIENCES OF THE EVALUATION OF EDUCATIONAL PROGRESS - Seiied Abdollah Hojjati; Mohammad Hossein Yarmohammadian; Narges Keshtiaray (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2017)
The present study is a phenomenological inquiry into the life experiences of Iranian engineering students on the educational progress of evaluation at university. For the purpose of the data collection, twelve engineering students, electronic, mechanics, industrial, aerospace, etc. were interviewed by the lead author. The participants volunteered for the study and each interview lasted approximately 35 minutes. The adapted design was flexibility and purposeful sampling. Qualitative data collection was employed for the present study. Data were analysed through inductive analysis and creative synthesis (Glaser's seven steps). The findings revealed important patterns and themes behind evaluation. The participants had the life experiences of evaluation as being unfair, not fully based on the classroom syllabus, and call for raising professors' awareness on evaluation. They advocated a synthesis of a theoretical and practical evaluation. The participants also supported formative evaluation during a semester. The present study has a number of pedagogical implications for teacher education, teachers, testing professionals, among others.